The influence of TikTok usage intensity on Islamic education learning outcomes of student - Taqiyya, Hedona Hilwa; Musfirotun, Latifah; Purnomo, Purnomo (TAWAZUN: Jurnal Pendidikan Islam, 2025)
This study was motivated by the high usage of TikTok among students, which has the potential to affect learning outcomes, particularly in Islamic Religious Education classes. The purpose of this study was to determine the relationship between the intensity of TikTok usage and PAI learning outcomes among 10th grade students at SMKN 3 Salatiga. This study employs a quantitative approach using a correlational survey method. A sample of 96 students was selected using purposive sampling, with criteria including active TikTok users and having received PAI grades in the current semester. Data was collected through a closed-ended questionnaire measuring the duration, frequency, and engagement of TikTok users, as well as documentation of academic performance grades. The analysis results indicate a positive correlation between the intensity of TikTok usage and PAI learning outcomes, meaning that the intensity of TikTok usage significantly influences PAI learning outcomes. This finding suggests the need for an adaptive learning approach tailored to students' digital habits to ensure that PAI content remains effectively conveyed. Abstrak Penelitian ini dilatarbelakangi oleh tingginya penggunaan TikTok di kalangan pelajar yang berpotensi memengaruhi hasil belajar, khususnya pada mata pelajaran Pendidikan Agama Islam (PAI). Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara intensitas penggunaan TikTok dan hasil belajar PAI pada siswa kelas X SMKN 3 Salatiga. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei korelasional. Sampel sebanyak 96 siswa dipilih menggunakan teknik purposive sampling, dengan kriteria pengguna aktif TikTok dan telah memperoleh nilai PAI pada semester berjalan. Data dikumpulkan melalui angket tertutup yang mengukur durasi, frekuensi, dan keterlibatan pengguna TikTok, serta dokumentasi nilai hasil belajar. Hasil analisis menunjukkan adanya hubungan positif antara intensitas penggunaan TikTok dengan hasil belajar PAI, yang berarti bahwa intensitas penggunaan TikTok berpengaruh signifikan terhadap hasil belajar PAI. Temuan ini mengindikasikan perlunya pendekatan pembelajaran yang adaptif terhadap kebiasaan digital siswa agar materi PAI tetap efektif tersampaikan.